Perception of Female Nurses and Nursing Students Regarding Polycystic Ovarian Syndrome Working in a Tertiary Hospital - Jewel Manzoor; Faiqa Khalid; Faisal Nadeem; Alishbah Shakir; Warda Tu Nisa; Jerry Zahid (Journal of Health, Wellness and Community Research, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age, often underdiagnosed due to varied clinical presentations and insufficient awareness among healthcare providers. Despite their critical role in women’s health education and early detection, the level of knowledge among nurses and nursing students regarding PCOS remains inadequately explored, especially in tertiary care settings in developing countries. Objective: This study aimed to assess the level of knowledge and awareness regarding PCOS, including its symptoms, diagnostic criteria, and treatment options, among female nurses and nursing students working in a teaching hospital in Lahore. Methods: A descriptive cross-sectional study was conducted among 95 female nursing students and staff nurses aged 18–26 years, recruited through random sampling. Participants with chronic illnesses were excluded. Data were collected using a validated 20-item questionnaire adapted from Haq et al. and distributed via an online Google Form. The study received ethical approval and was conducted in accordance with the Declaration of Helsinki. SPSS version 23 was used to analyze data through descriptive statistics and Pearson correlation to evaluate associations between demographic variables and knowledge scores. Results: The mean knowledge score was 72.36 (76.16%). While most respondents demonstrated awareness of symptoms such as irregular menstruation (93.7%) and hirsutism (86.3%), knowledge gaps were observed in diagnostic methods and long-term complications. A moderate negative correlation (r = –0.5, p = 0.01) was found between knowledge level and one demographic variable, indicating statistically significant associations. Conclusion: Although the majority of nurses and nursing students had general awareness of PCOS, critical gaps in diagnostic and management knowledge highlight the need for structured educational interventions. Enhancing reproductive health literacy among frontline nursing professionals can significantly improve early detection and patient outcomes.
Keywords: Polycystic Ovary Syndrome, Nurses, Nursing Students, Reproductive Health, Awareness, Knowledge, Cross-Sectional Studies.